2017
DOI: 10.1038/nrclinonc.2017.157
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma — evolving concepts and therapeutic strategies

Abstract: Cholangiocarcinoma is a disease entity comprising diverse epithelial tumours with features of cholangiocyte differentiation: cholangiocarcinomas are categorized according to anatomical location as intrahepatic (iCCA), perihilar (pCCA), or distal (dCCA). Each subtype has a distinct epidemiology, biology, prognosis, and strategy for clinical management. The incidence of cholangiocarcinoma, particularly iCCA, has increased globally over the past few decades. Surgical resection remains the mainstay of potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
1,159
0
26

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,245 publications
(1,197 citation statements)
references
References 178 publications
(242 reference statements)
12
1,159
0
26
Order By: Relevance
“…13 These advances in comprehensive whole-exome and transcriptome sequencing have defined the genetic landscape of each cholangiocarcinoma subtype, and potential promising molecular targets for precision medicine are being evaluated in clinical trials, 25 including those exploring immunotherapy. Thirtyfive percent of patients had received more than 2 lines of systemic treatments before the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 These advances in comprehensive whole-exome and transcriptome sequencing have defined the genetic landscape of each cholangiocarcinoma subtype, and potential promising molecular targets for precision medicine are being evaluated in clinical trials, 25 including those exploring immunotherapy. Thirtyfive percent of patients had received more than 2 lines of systemic treatments before the study.…”
Section: Discussionmentioning
confidence: 99%
“…22 The toxicity of the standard 160-mg regorafenib regime has resulted in the clinical use of various dose modifications, including dose reductions and interruptions. 23,25 Hypophosphatemia is one of the most common toxicities of regorafenib, with 5% to 9% rates of grade ≥3 toxicities reported in phase 3 studies. 39 The other study that analyzed data from patients with mCRC used different regorafenib starting doses: 54% of patients received 160 mg, 40% received 120 mg, and 6% received 80 mg. 40 Those results indicated that various starting doses had no association with survival in univariate or multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cholangiocarcinomas are neoplasms arising from epithelial cells of the biliary tract, and are the second most common primary liver malignancy . They can be divided according to their anatomical location.…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for only 3% of gastrointestinal malignancies, they are aggressive tumors usually marked by late diagnosis and poor outcomes . Surgery is still the most effective therapy available, and a complete tumor resection is important to achieve long‐term survival …”
Section: Introductionmentioning
confidence: 99%
“…No clear indications for second‐line chemotherapy exist. Given the limited survival advantage of GemCis, it has been suggested that some patients should be enrolled in experimental trials in place of standard‐of‐care . Any experimental trials should require careful biomarker‐driven stratification of prospective responders, given the potential of individual driver mutations to influence diverse pharmacologic responses .…”
mentioning
confidence: 99%